2022
DOI: 10.1021/acs.jpca.2c05023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porous Catalyst Support on Plasma-Assisted Catalysis for Ammonia Synthesis

Abstract: We report on the effect of catalyst support particle porosity on the conversion of NH3 synthesis from N2 and H2 in a coaxial dielectric barrier discharge (DBD) plasma reactor. The discharge was created using an AC applied voltage with the reactor at room temperature and near atmospheric pressure (550 Torr). Two different particles of almost equal diameter (∼1.5 mm)porous silica (SiO2) ceramic beads (average pore size: 8 nm) and smooth, nonporous soda lime glass beadswere compared in the DBD reactor. As the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
(141 reference statements)
0
14
0
Order By: Relevance
“…Ar 2 * is an electronically excited Ar 2 . Reactions for N and H species, including interactions between vibrationally and electronically excited species, radicals, ions, and surface species, were adapted from Hong et al as in our previous reports. , In our discussion of excited state chemistry, the electronically excited N 2 states N 2 ( C 3 Π u ), N 2 ( B 3 Π g ), and N 2 ( A 3 Σ u + ) are abbreviated as N 2 (C3), N 2 (B3) and N 2 (A3), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ar 2 * is an electronically excited Ar 2 . Reactions for N and H species, including interactions between vibrationally and electronically excited species, radicals, ions, and surface species, were adapted from Hong et al as in our previous reports. , In our discussion of excited state chemistry, the electronically excited N 2 states N 2 ( C 3 Π u ), N 2 ( B 3 Π g ), and N 2 ( A 3 Σ u + ) are abbreviated as N 2 (C3), N 2 (B3) and N 2 (A3), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the practical range of E/N that was explored (100–141 Td), E-R reactions always dominated over L-H reactions by similar orders of magnitude for the production of NH(s). The conditions (low reduced electric field) under which L-H reactions occur faster than E-R reactions and radical adsorption are challenging for plasma generation. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…100 The results of optical emission spectroscopy to identify excited species in the N 2 -H 2 plasma reaction using the DBD plasma in the presence of various catalysts have been reported by several research groups, as shown in Table 2. 80,91,93,[100][101][102] Although the mechanisms of ammonia synthesis in a non-thermal plasma catalysis system have been reported and described by several groups, [103][104][105][106][107][108][109] Hong et al have presented for the rst time a detailed kinetic modelling of nonequilibrium N 2 -H 2 atmospheric pressure discharges for catalytic NH 3 synthesis. 110 As we all know, to form ammonia in the gas phase, the bonds of both molecular hydrogen and molecular nitrogen must be broken.…”
Section: Reaction Mechanisms In Plasma-catalysis Ammonia Synthesismentioning
confidence: 99%
“…The nonthermal plasma is convenient to combine with the heterogeneous catalyst. In general, this hybrid system may synergistically improve the conversion rate and selectivity. Despite a lot of efforts, due to the complex interaction between plasma and catalyst, , a deep and thorough understanding of the associated mechanism is still lacking. On one hand, the presence of a catalyst affects the discharge type and the performance of plasma.…”
Section: Introductionmentioning
confidence: 99%